2005
DOI: 10.1103/physrevb.71.184443
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of oxygen-stabilized tetragonal Ni nanoparticles prepared by borohydride reduction method

Abstract: We report a comprehensive study on the structure and magnetic properties of ultrafine Ni nanoparticles prepared by the borohydride reduction method. A spontaneous surface oxide layer of NiO encapsulates the Ni particles, as these have been prepared under ambient atmosphere. From the x-ray diffraction ͑XRD͒ pattern, the "as-prepared" sample has been identified as Ni in a tetragonal crystal structure, stabilized by the incorporation of oxygen atoms in the Ni lattice. On annealing this sample in air at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 37 publications
5
59
1
Order By: Relevance
“…The diffraction pattern shows five clear peaks and all these peaks could be indexed to Fm3m crystalline Ni phase indicating that the powder has a single phase microstructure. Recently, it has been reported that aqueous state reduction results in the formation of tetragonal solid solution of oxygen in Ni͑O͒, which was found to be stable up to 573 K. 15 A metastable hexagonal Ni phase has also been reported to form during solution synthesis which exhibits an antiferromagnetic behavior. 16 The formation of an intermediate compound such as Ni 2 B under anaerobic conditions has also been reported earlier.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction pattern shows five clear peaks and all these peaks could be indexed to Fm3m crystalline Ni phase indicating that the powder has a single phase microstructure. Recently, it has been reported that aqueous state reduction results in the formation of tetragonal solid solution of oxygen in Ni͑O͒, which was found to be stable up to 573 K. 15 A metastable hexagonal Ni phase has also been reported to form during solution synthesis which exhibits an antiferromagnetic behavior. 16 The formation of an intermediate compound such as Ni 2 B under anaerobic conditions has also been reported earlier.…”
Section: Resultsmentioning
confidence: 99%
“…The so-formed metallic Ni seems to be chemically stable in the aqueous solution, in the presence of oxygen, and even through a thorough washing process. This can be explained by the formation of a stable surface oxide layer of NiO/Ni(OH) 2 on each individual Ni particle, [41] as has been revealed by XPS, though this layer must be very thin, since it cannot be clearly identified in HRTEM images. It is still puzzling that if the process occurs through hydrazine decomposition on the platinum surface and through further Ni growth, why do the shells not selectively form on the Pt tips, but rather cover the whole rods, regardless of shell thickness.…”
mentioning
confidence: 96%
“…It was found that particles of size 1-4 nm had hcp structure, while larger particles had fcc structure. Later Roy et al (2005) also prepared nickel nanoparticles by borohydride reduction in water in ambient conditions, but instead of hcp nickel nanoparticles they obtained yet another crystalline structure, which they identified as tetragonal with an O atom sitting in the middle of the unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…Hcp Ni nanoparticles of size about 9 nm have been shown to be paramagnetic (Jeon et al, 2006). On the other hand, Roy et al (2005) assigned an oxygen-stabilized tetragonal crystal structure for Ni particles obtained using the borohydride reduction to explain the paramagnetism of their 20 nm sized self-supported particles.…”
mentioning
confidence: 99%